Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T20:49:05+01:00
A 12,4-2,4:(-2 4/3)+2 2/3*(0,9)-0,1 =12 4/10-24/10*(-4/10)=8/3*9/10-1/10=12 4/10+24/25+24/10-1/10=12 4/10=12 4/10=24/25=23/10=12 40/250=240/250=230/250=14 3/24
b -[-(7 1/3):1,1-1,1 * 6 2/3]+4 1/6 * (-4) =-[-(7 1/3):11/10-11/10*20/3]=25/3*(4)=-[-7 11/3*11/10*20/3]-50/3=-[-121/15-22/3]-50/3=-[-121-110/15]-50/3=-[-231/15]-50/3=231/15-50/30=181/15-50/30=462/30-50/30=412/30=13 22/30
c) [0,8-(1,2 * 5/12-0,8)]:(-1/8) =[8/10-(12/10*5/12-8/10]*(-8/10)=[8/10-(5/10-8/10)]*(-8/10=11/10*-8/1)=-44/5= 8 4/5
2010-02-23T20:50:19+01:00
A) 12,4 -2,4 : ( -2 4/3)+2 2/3* 0,9 - 0,1 = 124/10 - 24/10 : 10/3 + 8/3 * 9/10 - 1/10= 124/10 + 8/1 + 72/30 - 1/10 = 372/30 + 240/30 +72/30- 3/30 = 681/30 = 22,7

b)-[-(7 1/3):1,1-1,1 * 6 2/3]+4 1/6 * (-4) =-[-(22/3) : 11/10 - 11/10 *20/3]+ 25/6 * (-4/1)=-[-(22/3 *10/11 -22/3]+25/6 * (-4/1)=-[-(20/3)-22/3]-100/6=20/3 + 22/3 - 100/6 = 44/3 - 100/6 = 88/6 - 100/6 =12/6 = 2

c) [0,8-(1,2 * 5/12-0,8)]:(-1/8) = [0,8 - 1,2 * (-5/12)+ 0,8]: (-1/8)=[1,6-1,2 *(-5/12)]:(-1/8)=[1,6-12/10*(-5/12)]:(-1/8)=1,6+1/2 *8=1,6 - 4= -2,4